Impaired interferon‐α expression in plasmacytoid dendritic cells in asthma - Ting‐Yu Lin; Chun‐Yu Lo; Kuo‐Chien Tsao; Po‐Jui Chang; Chih‐His Scott Kuo; Yu‐Lun Lo; Shu‐Min Lin; Meng‐Heng Hsieh; Tsai‐Yu Wang; Ping‐Chih Hsu; Horng‐Chyuan Lin (Immunity, Inflammation and Disease)
Abstract Background Toll‐like receptor (TLR)‐7‐associated rhinovirus (RV) activation is involved in the pathogenesis of asthma. Plasmacytoid dendritic cells (pDCs) are the main interferon‐α‐producing cells against viruses. Objective To determine whether asthmatic patients and control subjects differ in terms of interferon‐α expression in pDCs under TLR‐7 or RV stimulation. Methods pDCs were identified in BDCA‐2+ and HLA‐DR+ peripheral blood mononuclear cells. Interferon‐α expression of pDCs was analyzed after TLR‐7 stimulation with or without interleukin 4 (IL‐4)/IL‐13 pretreatment. Interferon‐α expression was also analyzed after RV stimulation over periods of 24, 48, or 96 h with or without IL‐4 pretreatment. RV detection and molecular typing were assayed from throat swabs. Results Following TLR‐7 stimulation, the expression of intracellular interferon‐α was higher in the pDCs of normal subjects than those of asthmatic patients; however, pretreatment with IL‐4 was shown to reduce this effect. After 48‐ and 96‐h RV stimulation, we observed a notable increase in the production of interferon‐α of pDCs in normal subjects but not in asthmatic patients. Baseline interferon‐α expression in pDCs and the incidence of asthma exacerbation to emergency was higher among the 13% of patients identified as rhinovirus+ than among their RV counterparts. Conclusion Our study discovered the response to TLR‐7 stimulation in pDCs was compromised and the sustainability of interferon‐α expression to RV stimulation was reduced in pDCs of asthmatic patients, which provide further evidence of defective innate response and subspeciality to RV infection in asthma. The high exacerbation history founded in RV+ patients agrees with these findings. Further research is required for the modulatory effect of IL‐4 on TLR‐7 stimulated pDCs.